The Influence Of Loan To Deposit Ratio (Ldr) And Operational Cost Towards Operational Income (Bopo) Against Return On Assets - Nababan, Daniel (International Journal of Psychosocial Rehabilitation, 2020)
A bank is one of the financial institutions whose main activity is to collect funds from the community and then distribute them with the aim to earn a profit. This study aims to empirically examine the influence of Loan to Deposit Ratio (LDR) and Operational Cost to Operational Income (BOPO) on Return on Assets (ROA) on Banking Company Listed in Indonesia Stock Exchange Period 2014-2018. This research uses the purposive sampling technique. The data used in this study is secondary data from annual financial reports that have been published by banking companies listed on the Indonesia Stock Exchange. The data were analyzed using descriptive statistic analysis, the classic assumption test, multiple regression analysis, determination coefficient analysis (R2), and hypothesis testing using the ttest and Ftest with a 5% significance level. The results of this study indicate that partially Loan to Deposit Ratio (LDR) has a positive influence on Return on Assets (ROA) and Operational Cost to Operational Income (BOPO) has a negative influence on Return on Assets (ROA). While simultaneously, Loan to Deposit Ratio (LDR) and Operational Cost to Operational Income (BOPO) have influence on Return on Assets (ROA).